The quality of Students learning Outcomes of Senior High School Using Discovery Learning Model for the Human Respiratory System Discussion (Case in SMA Negeri 1 Panai Tengah Senior High School) || Kualitas Hasil belajar Siswa SMA Negeri 1 Panai Tengah Menggunakan Model Pembelajaran Discovery Terhadap Materi Sistem Respirasi Manusia - Tarjuriah, Tarjuriah; Harahap, Risma Delima (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2021)
This research was conducted at SMA Negeri I Panai Tengah in the 2019/2020 academic year. This study aims to determine the effect of the application of the discovery learning model on student learning outcomes in the human respiration system Discussion in Second class of Senior High School (XI IPA). This type of research is a quasi-experimental. The population were all students of class XI IPA SMA Negeri I Panai Tengah that amount 32 individu . The sampling technique were total sampling, where the entire population would been the sample in this study. The instruments used were tests, observation sheets and questionnaires. Data were analyzed using descriptive statistics, prerequisite tests and hypothesis testing with the help of SPSS version 22 software. From the results of hypothesis analysis showed the paired sample t-test (paired sample t-test), obtained tcount values of 5,422 and t table with ᾳ= 0,05, degree of freedom (dk)=15, then the t table value is 2.131. the value of t count > t table or 5.422 > 2.131 can be concluded that H0 is rejected and Ha is accepted. This means that there is a significant effect of the application of the discovery learning model on student learning outcomes in class XI IPA SMA Negeri I Panai Tengah in the 2019/2020 learning year.Penelitian ini dilakukan di SMA Negeri I Panai Tengah tahun pembelajaran 2019/2020. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran Discovery terhadap hasil belajar siswa pada materi sistem Respirasi manusia di kelas XI IPA. Jenis penelitian ini adalah kuasi eksperimen. Populasi, seluruh siswa kelas XI IPA SMA Negeri I Panai Tengah berjumlah 32 orang. Teknik pengambilan sampel adalah total sampling, dimana seluruh populasi menjadi sampel dalam penelitian. Instrumen yang digunakan adalah tes, lembar observasi dan angket. Data dianalisis menggunakan statistik deskriptif, uji prasyarat dan uji hipotesis dengan bantuan software SPSS versi 22.Dari hasil uji hipotesis, uji-t sampel berpasangan (Paired Sample t-test), diperoleh nilai thitung sebesar 5, 422 dan ttabel dengan α = 0,05, dk = 15 maka diperoleh nilai ttabel sebesar 2,131. Nilai thitung > ttabel atau 5,422 > 2,131 dapat disimpulkan bahwa H0 ditolak dan Ha diterima. Artinya terdapat pengaruh yang signifikan dari penerapan model pembelajaran Discovery terhadap hasil belajar siswa di kelas XI IPA SMA Negeri I Panai Tengah tahun pembelajaran 2019/2020